2021
DOI: 10.1080/15438627.2021.1896517
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular buffer choice influences acid-base responses and gastrointestinal symptoms

Abstract: To compare the bicarbonate kinetics and gastrointestinal (GI) symptom responses between an equal dose of sodium bicarbonate and sodium citrate using delayed-release capsules. Thirteen active males (age 20.5 ± 2.1 y, height 1.8 ± 0.1 m and body mass [BM] 76.5 ± 9.6 kg) consumed either 0.3 g . kg −1 BM sodium bicarbonate, sodium citrate or a placebo, using a double-blind, randomized crossover design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 30 publications
4
9
1
Order By: Relevance
“…The similar peak alkalosis observed here is in accordance with the sole prior investigation to compare these supplements using the same doses as the current study (Potteiger et al, 1996). Ingestion of equal SC and SB doses (300 mg/kg BM) has previously returned equivocal blood alkalosis comparisons (Kumstát et al, 2018;Parry-Billings & MacLaren, 1986;Peacock et al, 2021;Tiryaki & Atterbom, 1995). One of these studies reported that SB elicited greater alkalosis compared with SC (Peacock et al, 2021), and earlier investigations reported no difference between the supplements for indicators of magnitude of blood alkalosis (Kumstát et al, 2018;Parry-Billings & MacLaren, 1986;Tiryaki & Atterbom, 1995).…”
Section: Magnitude and Timing Of Induced Blood Alkalosissupporting
confidence: 89%
See 3 more Smart Citations
“…The similar peak alkalosis observed here is in accordance with the sole prior investigation to compare these supplements using the same doses as the current study (Potteiger et al, 1996). Ingestion of equal SC and SB doses (300 mg/kg BM) has previously returned equivocal blood alkalosis comparisons (Kumstát et al, 2018;Parry-Billings & MacLaren, 1986;Peacock et al, 2021;Tiryaki & Atterbom, 1995). One of these studies reported that SB elicited greater alkalosis compared with SC (Peacock et al, 2021), and earlier investigations reported no difference between the supplements for indicators of magnitude of blood alkalosis (Kumstát et al, 2018;Parry-Billings & MacLaren, 1986;Tiryaki & Atterbom, 1995).…”
Section: Magnitude and Timing Of Induced Blood Alkalosissupporting
confidence: 89%
“…Ingestion of equal SC and SB doses (300 mg/kg BM) has previously returned equivocal blood alkalosis comparisons (Kumstát et al, 2018;Parry-Billings & MacLaren, 1986;Peacock et al, 2021;Tiryaki & Atterbom, 1995). One of these studies reported that SB elicited greater alkalosis compared with SC (Peacock et al, 2021), and earlier investigations reported no difference between the supplements for indicators of magnitude of blood alkalosis (Kumstát et al, 2018;Parry-Billings & MacLaren, 1986;Tiryaki & Atterbom, 1995). It remains unclear why there is this inconsistency; however, a possible explanation may include variations in the timing and duration of the postingestion blood sampling across previous investigations, and may also be contributed to by differing sampling sites (i.e., venous, arterial, and capillary) and presampling procedures (e.g., arterialization) across studies.…”
Section: Magnitude and Timing Of Induced Blood Alkalosismentioning
confidence: 99%
See 2 more Smart Citations
“…A handful of older studies have profiled changes in acid-base balance after CIT ingestion (Kowalchuk et al, 1989;McNaughton, 1990), but these were ingested in solution and in a fasted state. A more recent body of evidence would suggest time-to-peak increase in [HCO 3 − ] after CIT ingestion is often protracted when compared with BIC (Peacock et al, 2021;Urwin et al, 2021). This might explain the discrepancy in the present study, as the relative rise in both pH and HCO 3 − was slower in the CIT condition, compared with BIC, and ultimately lower at 180 min (Figure 2a and 2b).…”
Section: Discussioncontrasting
confidence: 65%